2009
DOI: 10.3748/wjg.15.1273
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal papillary mucinous neoplasm in chronic calcifying pancreatitis: Egg or hen?

Abstract: Intraductal papillary mucinous neoplasm (IPMN) is an increasingly reported entity. Extensive pancreatic calcification is generally thought to be a sign of chronic pancreatitis, but it may occur simultaneously with IPMN leading to diagnostic difficulties. We report a case of a patient initially diagnosed with chronic calcifying pancreatitis who was later shown to have a malignant IPMN. This case illustrates potential pitfalls in the diagnosis of IPMN in the case of extensive pancreatic calcification as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Several mechanisms that might explain the occurrence of pancreatic calcification in patients with IPMN have been suggested. One possible mechanism is that the blocking of the pancreatic duct by a mucin plug might be responsible for the formation of pancreatic calcification . Intestinal type IPMN has been reported to belong to the hypermucin secretion type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms that might explain the occurrence of pancreatic calcification in patients with IPMN have been suggested. One possible mechanism is that the blocking of the pancreatic duct by a mucin plug might be responsible for the formation of pancreatic calcification . Intestinal type IPMN has been reported to belong to the hypermucin secretion type.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism is that the blocking of the pancreatic duct by a mucin plug might be responsible for the formation of pancreatic calcification. 12,18 Intestinal type IPMN has been reported to belong to the hypermucin secretion type. Therefore, we hypothesized that the intestinal type might be related to pancreatic calcification, but no significant association was detected between the mucin phenotype and pancreatic 0.0002 0.001 0.006 † The scores shown were awarded as follows: 0 (absent) and 1+ (present).…”
Section: Discussionmentioning
confidence: 99%
“…In our series, four of five cases have the similar appearance. Additionally, calcification was also observed in CCs, and the most likely explanation for the calcification in CCs is the presence of thick mucin, which has the tendency to build up calcium salt deposits ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mucin has usually the same pattern of pancreatic juice with the different imaging techniques (hypoechoic at US, hypodense at CT, hyperintense on T2-weighted images, and hypointense on T1-weighted images at MRI), thus it is not possible to differentiate mucin from pancreatic juice. Although some authors suggested that with DWI is possible to differentiate the content of cystic lesions of the pancreas [75], there is a significant overlap in ADC values between pancreatic juice, IPMN, serous cystadenoma (SCA), and mucinous cystadenoma.…”
Section: Imaging-pathologic Correlationmentioning
confidence: 99%
“…Extensive pancreatic calcifications are generally thought to be a sign of chronic pancreatitis, but it may occur simultaneously with IPMN leading to diagnostic difficulties [75].…”
Section: Pitfalls and Errorsmentioning
confidence: 99%